Challenges Faced by International Students: A Case Study of Jambi’s Institute of Higher Learning - Sri Wachyunni; Mukhlash Abrar; Istifada Istifada; Hary Soedarto Harjono; Robi Hendra (UIN Sultan Aji Muhammad Idris Samarinda, 2023)
Although there have been many studies investigating international students, many of them focused on the students who travel in pursuit of higher education in English countries and/or universities. This current qualitative study is intended to explore the experiences of international students, particularly the challenges, and strategies to deal with the challenges and the culture shock while studying in Jambi, Indonesia. In order to collect the data, a semi-structured interview was employed and guided by an interview protocol to stimulate the participants in answering the questions during the interview. The participants of this study were nine international students who studied at one public university in Jambi. Through thematic analysis, we found that international students faced some challenges living and studying in Jambi, such as language issues, academic issues, individual issues, and living style and related issues. To overcome the challenges, international students employed two main strategies, including self-management strategies and seeking help. Moreover, although the culture of international students is quite similar to the culture of the hosting country, we identified a lack of foreigner sense and physical contact as the culture shocks experienced by one international student. Looking at the challenges and culture shocks experienced by international students, this study suggests that preparation is crucial for prospective international students before pursuing their studies overseas.